1989
DOI: 10.1007/bf00554168
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila purine auxotrophy: New alleles ofadenosine2 exhibiting a complex visible phenotype

Abstract: New mutant alleles of the adenosine2 locus (ade2; 2-17.7) have been isolated using the eye-color phenotype exhibited by the prototype auxotrophic allele ade2 as the screening criterion. The new mutants form a single complementation group, suggesting that they all exhibit purine auxotrophy and defective formylglycineamide ribotide amidotransferase enzyme, like ade2. Tests carried out on particular new alleles confirm these suggestions. The new mutants all exhibit more extreme physical defects than the prototype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 18 publications
3
15
0
Order By: Relevance
“…Pigmentation in these mutants is normal, however. Additionally, de novo pyrimidine mutants in Drosophila often possess defects in wing formation (Rawls and Fristrom, 1975;Falk, 1976), whereas mutants in de novo purine biosynthesis have defects in eye color (Tiong et al, 1989). These studies, when combined with our results, support a model in which de novo purine biosynthesis and de novo pyrimidine biosynthesis play important but tissue-specific roles during animal development.…”
Section: Research Articlesupporting
confidence: 82%
See 2 more Smart Citations
“…Pigmentation in these mutants is normal, however. Additionally, de novo pyrimidine mutants in Drosophila often possess defects in wing formation (Rawls and Fristrom, 1975;Falk, 1976), whereas mutants in de novo purine biosynthesis have defects in eye color (Tiong et al, 1989). These studies, when combined with our results, support a model in which de novo purine biosynthesis and de novo pyrimidine biosynthesis play important but tissue-specific roles during animal development.…”
Section: Research Articlesupporting
confidence: 82%
“…Perhaps the most well-studied model for the function of the de novo purine synthesis pathway during development comes from work in Drosophila, in which mutations in prat (ppat) (Clark, 1994), ade2 (pfas) (Henikoff et al, 1986b;Johnstone et al, 1985), ade3 (gart) (Henikoff et al, 1986a;Johnstone et al, 1985) and ade5 (paics) (O'Donnell et al, 2000) have been identified, as well as mutations in the GTP pathway components IMPDH (raspberry) and GMP synthase (burgundy) (Johnstone et al, 1985;Long et al, 2006). Each of these de novo pathway mutants shows a subset of developmental defects that have collectively been termed the 'purine syndrome' phenotype (Tiong et al, 1989). Purine syndrome defects include a reduction in the red pteridine-derived eye pigments, bristle and leg malformations, small wings, and pupal lethality (Tiong et al, 1989).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To ask whether the lethal phenotype caused by double RNAi for Prat and Prat2 has a similar phenotype as that caused by the mutations of single-copy genes that act downstream in the de novo purine pathway, we characterized the pupal lethal phenotype of ade2 by crossing two EMS-induced ade2 lethal alleles (ade2 3 and ade2 4 ) (Tiong et al 1989). We found that 8% of ade2 3 /ade2 4 pupae arrested at the P2 stage with defects in eversion of the anterior spiracle and failure of gas bubble movement (Table 5 and Figure 4C), which is very similar to the earliest arrested prepupae caused by double RNAi for Prat and Prat2 ( Figure 4B).…”
Section: A6mentioning
confidence: 99%
“…PAICS is highly conserved in higher eukaryotes, and mutations in PAICS can result in developmental defects and in some cases embryonic lethality (Tiong et al 1989;Ng et al 2009). Additionally, because cancer cells rely heavily on the de novo purine biosynthesis pathway while normal cells preferentially utilize salvage pathways (Li et al 2007), PAICS has emerged as a potential target for anticancer drugs.…”
Section: Weeks 4-7: Using Yeast To Study Enzyme Defectsmentioning
confidence: 99%